Reclaiming Food Governance: Social Movements and Sustainable Food Systems - Rulinawaty, Rulinawaty; Samboteng, Lukman; Andriyansah, Andriyansah; Alwi, Alwi (AGUSPATI Research Institute, 2025)
This study examines how civil society organizations and social movements engage with governance processes to achieve equitable, sustainable, and democratic transformations in food systems. Using a comparative qualitative approach, the research investigates case studies from Canada, New Zealand, France, and the United States to analyze varying governance models, including multi-stakeholder governance, collaborative governance (co-governance), and polycentric or self-governance. Results demonstrate that civil society participation within multi-stakeholder frameworks can influence policy discourses but faces significant constraints from state and private sector actors. Collaborative governance arrangements show greater potential, allowing civil society to meaningfully co-produce food governance outcomes; however, such partnerships often require movements to make pragmatic compromises. Polycentric governance and self-governance models enable civil society actors to exercise greater autonomy, particularly benefiting Indigenous and local communities, although institutional recognition remains a critical challenge. Overall, this study contributes a nuanced understanding of how social movements strategically mobilize power to reshape food governance systems, highlighting opportunities, constraints, and conditions that influence their ability to advance transformative agendas towards sustainability, social justice, and democracy in food systems governance.